2020
DOI: 10.1177/1045389x20969916
|View full text |Cite
|
Sign up to set email alerts
|

Embedded piezoelectric transducers based early-age hydration monitoring of cement concrete added with accelerator/retarder admixtures

Abstract: Accelerator/retarder admixtures are often added into concrete to improve its early-age strength, which needs to be effectively monitored during its hardening process. The electromechanical impedance (EMI) technique has validated its effectiveness for concrete hydration monitoring, this study attempted to extend the EMI technique to monitor 28-day age of strength gain in concrete that added with accelerator/retarder admixtures. Two types of new piezoelectric (PZT) transducers namely cement/aluminum embedded PZT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…For the impedance-based SHM methods, the monitoring results mainly depend on the selections of effective frequency bands [ 46 , 47 ]. Meanwhile, the sensitive frequency bands are dependent on the material properties and geometric sizes of the smart aggregate’s components [ 24 , 48 ]. In general, the sensitive frequency band relies on the orientation of the sensors in the target structures.…”
Section: Pzt-embedded Smart Rock For Impedance-based Concrete Damamentioning
confidence: 99%
See 1 more Smart Citation
“…For the impedance-based SHM methods, the monitoring results mainly depend on the selections of effective frequency bands [ 46 , 47 ]. Meanwhile, the sensitive frequency bands are dependent on the material properties and geometric sizes of the smart aggregate’s components [ 24 , 48 ]. In general, the sensitive frequency band relies on the orientation of the sensors in the target structures.…”
Section: Pzt-embedded Smart Rock For Impedance-based Concrete Damamentioning
confidence: 99%
“…The differences could come from an inaccurate thickness of the epoxy layer among the coated PZT sensors. The previous study showed that the thickness of the adhesive layer had significant impedance responses [ 48 , 52 ]. Despite that, the FE tool was applicable for the analysis of the impedance responses of the PZT-embedded smart rock.…”
Section: Pzt-embedded Smart Rock For Impedance-based Concrete Damamentioning
confidence: 99%
“…Furthermore, the sensitivities of embeddable PZT sensors depend on the material properties of their components (e.g., epoxy, concrete) [ 22 , 30 ]. Thus, an appropriate design of the smart rebar or aggregate should be achieved to detect relatively small stress changes in PSC structures during long-term operation.…”
Section: Discussion On Smart Rebar–aggregate Sensor In Psc Anchoragementioning
confidence: 99%
“…The impedance features measured from surface-bonded PZT sensors were strongly influenced by an environmental ambient, thereby demanding a complex algorithm to compensate for the environmental effects [ 28 , 29 ]. Additionally, many researchers have attempted to embed PZT sensors in concrete structures for monitoring curing-induced strength changes and hydration-induced stress variations [ 30 , 31 , 32 ]. In their works, brittle PZT sensors were commonly treated by protective layers to form small concrete blocks before embedding them into inspected structures.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the technique, lots of researchers have successfully detected the electric impedance variations of the transducer as a result of changes in the mechanical impedance of the host structure. The EMIbased method has been extensively applied in many aspects of structural health monitoring including concrete hydration (Ai et al, 2020;Jothi Saravanan et al, 2017), interfacial debonding (Li et al, 2018a(Li et al, , 2018b, crack monitoring (Lim and Soh, 2014;Na and Baek, 2018), corrosion of metallic structure (Park and Park, 2010;Talakokula and Bhalla, 2015). Many significant progresses have been made in both theoretical models and engineering applications.…”
Section: Introductionmentioning
confidence: 99%